Utilization of laboratories through scientific literacy activities to improve scientific attitudes and creative thinking - Nimreskosu, Asna Collins; Leiwakabessy, Fredy; Wael, Syahran (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2024)
One way to empower students' potential is by providing and utilizing laboratories, however, in several high schools in the Tanimbar Islands Regency, only a handful of teachers use laboratories as a means. biology learning for practical work in the process of teaching and learning activities, while most only deliver learning material without any practical activities in the laboratory. The aim of this research is to determine the effect of using laboratories through scientific literacy activities on the scientific attitudes and creative thinking of high school students in the Tanimbar Islands Regency. This type of research was quasi-experimental research. The population is all class X students of Tanimbar Islands State high school 8, Tanimbar Islands State high school 10, Tanimbar Islands State high school 12, totaling 75 students. Data analysis used Anova and continued with the Duncan test with the help of SPSS Version 27. The results showed that the use of laboratories through scientific literacy activities had an effect on the scientific attitudes of high school students in the Tanimbar Islands Regency with a value of sig. amounting to 0.018 < 0.05 and the use of laboratories through scientific literacy activities has an effect on the creative thinking of high school students in the Tanimbar Islands Regency with a sig value of 0.030 < 0.05.